Determination of Optimal Cut Point Temperatures at Crude Distillation Unit using the Taguchi Method - Ali, Syed Faizan (2012)
This paper proposes a technique for optimizing crude cut points. Taguchi method is applied in the selection of the significant variables and their respective optimal levels for a fractionation process. The variables considered were the cut point temperatures of products, namely, naphtha, kerosene, light and heavy diesels, atmospheric gas oil and the residue. The variables were assigned lower and upper bounds with a difference of ± 13.9°C (± 25°F) from the standard straight-run cut points. A steady-state model of a Crude Distillation Unit (CDU)is used as a virtual plant to carry out the fractionation of 100 kilo barrels per day of crude oil. Straight-run cases comprising of three Malaysian crude oils, namely, Bunga Kekwa, Bintulu and Tembungo, were analyzed as single, binary and ternary crude feeds. In each case, an optimal configuration of variables was determined by minimizing the energy required for the production of one kilo barrel/day of diesel.